At-Sea Associations in Foraging Little Penguins - Berlincourt, Maud (Public Library of Science, 2014)
Prey distribution, patch size, and the presence of conspecifics are important factors influencing a predator’s feeding tactics, including the decision to feed individually or socially. Little is known about group behaviour in seabirds as they spend most of their lives in the marine environment where it is difficult to observe their foraging activities. In this study, we report on at-sea foraging associations of little penguins (Eudyptula minor) during the breeding season. Individuals could be categorised as (1) not associating; (2) associating when departing from and/or returning to the colony; or (3) at sea when travelling, diving or performing synchronised dives. Out of 84 separate foraging tracks, 58 (69.0%) involved associations with conspecifics. Furthermore, in a total of 39 (46.4%), individuals were found to dive during association and in 32 (38.1%), individuals were found to exhibit synchronous diving. These behaviours suggest little penguins forage in groups, could synchronise their underwater movements and potentially cooperate to concentrate their small schooling prey.